Sistem Informasi Pelayanan Anggota DPD Akli Jawa Tengah Berbasis Web: (Studi Kasus di DPD AKLI Jawa Tengah) - Yono Yono; Dendy Kurniawan; Didik Sofian Haryadi (Pusat Riset dan Inovasi Nasional, 2023)
DPD AKLI Jawa Tengah , as one association engaged in the construction services of electricity, with members spread throughout Central Java, the development is still in need of a strategic plan and bring progress to the association and members. Therefore, in this paper the author will make a model of the registration certificate Web-based business entities that are expected to be one of the association's own development solutions.Member Services Information System developed by the method of approach to the development of systems with SDLC (System Development Life Cycle) results in an application that would address the needs of DPD AKLI Jawa Tengah will be a system of information services in order to enhance better service to members. In making this system, the authors use Macromedia Dreamweaver MX 2004 as a media design and PHP as the programming language used, and the MySQL database as a storage medium. The results of designing Member Services Information System can be accessed by members, assessors, and responsibility, whereby members can submit it online Business Enterprise certification. Assessors can assess more quickly and the approval of the person in charge can be done faster, so overall Business Enterprise certification process can be done more quickly and effectively.